Foreigners and Their Food: Constructing Otherness in Jewish, Christian, and Islamic Law By David M. Freidenreich (Berkeley: University of California Press, 2011. 325 pages.) (American Journal of Islam and Society, 2012)
Are dietary religious laws an obstacle to community relations between membersof the Abrahamic faiths? The new edition of Pierre Birnbaum’s Le Peupleet Les Gros, under the title Genèse du Populisme (Hachette Pluriel: 2012) exploreshow eating pork in Paris and other cities can be read as a sign of identitycrisis in French society, as a way of excluding from the public space thosewho are different, in this case Jews and/or Muslims who follow dietary lawsforbidding its consumption. Similarly, in Foreigners and Their Food: ConstructingOtherness in Jewish, Christian, and Islamic Law, the question ofcommunity, religious laws about food, and a thorough analysis of the relevantsacred texts is revealing. This book explores how the Abrahamic faiths conceptualize“us” and “them” through the rules related to food preparation bythose who are not “us” and the precise act of eating with “them.” Moreover,it echoes an important marker of how communities remain segregated at mealtime even though sharing food is seen as a familial, communal, and, most importantly,a sacred act.Foreigners and Their Food opens with Freidenreich’s personal strugglewith food and its significance in deconstructing boundaries between differenttraditions. The author, an ordained rabbi, readily admits to a bias of comparativeanalysis when interpreting the texts and laws; however, this admissionaccentuates and delineates a thorough analysis and rich interpretation that thestudy of religion is yearning for in intertexual analysis.The book begins with a discussion of “imagining otherness,” one thatalerts readers to the significance of food, its symbolic nature of inclusion/exclusion, and the absence of any analysis as to how it impacts so many religiousadherents who rely upon these laws but cannot critically reflect uponthem as markers of “us” and “them.” Freidenreich looks at what Leviticus,Deuteronomy, and similar traditional texts state, but he is clearly reaching formeanings that lie beyond the text. He points out as a general theme that “Absentfrom Biblical passages regarding these dietary laws, however, is any suggestionthat the norms enjoined upon Israelites stand in opposition tonon-Israelite practices” (p. 21) ...